Seasonal Treatment of an Infectious Disease is a Social Driver of Sustained Oscillations in the Disease incidence - Osuna, O.; Villavicencio Pulido, J. G. (Trends in Computational and Applied Mathematics, 2021)
We analyze a seasonal $SIR$ model that assumes a periodic treatment rate. Using the Leray-Schauder degree theory, we prove that model shows periodic solutions. This result shows that sustained oscillations in the incidence of the disease are related to the periodic application of a treatment against the disease. So, we can say that the periodic application of treatment can be considered a seasonal driver of the sustained oscillations.